Reaching beyond the break : effective police collaboration in the Caribbean - Adams, Yeon (Crystal Spirit Publishing, Inc. North CarolinaUS, 2018)
Presents data that identifies vulnerabilities that are leading to the Region vastly becoming known as "the most dangerous region in the world". It also describes the need for action by identifying the vulnerabilities with the use of data and providing recommendations for working towards a resolution.